Colloidal characteristics, emulsifying activities, and interfacial properties of α-lactalbumin–chitosan electrostatic complexes: effects of mass ratio and pH. Issue 2 (11th February 2020) - Liu, Yuexiang; Fan, Yuting; Wu, Xuli; Lu, Yujuan; Yi, Jiang
Abstract : Essential hydrophobic carrier properties of α-lactalbumin (α-LA) : chitosan (CHI) including mass ratio and pH have significant impacts on the characteristics, emulsifying activities, and interfacial properties of α-LA–CHI complexes. Abstract : The effects of essential hydrophobic carrier properties of α-lactalbumin (α-LA) : chitosan (CHI, M w 100 kDa, degree of deacetylation 75–85%) including mass ratio and pH on the characteristics, emulsifying activities, and interfacial properties of α-LA–CHI complexes were investigated. The interaction between α-LA and CHI was dominated by electrostatic interactions. Soluble α-LA–CHI complexes can be formed at both pH 6.0, and 6.5 at mass ratios of 1 : 1, 2 : 1, and 5 : 1, as shown by their optical appearance. UV-vis spectra demonstrated that the interaction between α-LA and CHI is highly CHI concentration, and pH-dependent. AFM graphs confirmed that α-LA–CHI complexes were spherical in shape and homogeneously dispersed in solution. The diameters of α-LA–CHI complexes were found to be around 100–250 nm, which was in accordance with DLS results, even though some aggregates were observed for the 1 : 1 α-LA–CHI complex. The emulsifying activity of α-LA was enhanced by complexation with CHI. Both the emulsifying activity index (EAI) and emulsifying stability index (ESI) of α-LA–CHI complexes were associated with mass ratio and pH values. The interfacial tension of α-LA–CHI complexes was negatively exponentially correlated with the EAI. The lower the interfacial tension of α-LA–CHI complexes on the oil–water interface, the higher the EAI. The results obtained from this study were complementary and provided insights into the interaction between α-LA and CHI, and suggested that α-LA–CHI complexes can be utilized as effective food ingredients for stabilizing, protecting, and delivering hydrophobic nutraceuticals.